Management of Adult Chiari I Patients Based on CSF Flow Magnetic Resonance Imaging: Experience of Two Neurosurgical Centers - Abdallah, Anas; Çınar, İrfan; Gündağ Papaker, Meliha; Güler Abdallah, Betül; Emel, Erhan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background and Study Aims Chiari malformation type 1 (CM1) is one of the most discussed neurosurgical disorders. No consensus exists how to manage adult CM1 patients. We aimed to evaluate all adult CM1 patients consecutively managed at our institutions and discuss our approach based on the phase-contrast (PC) magnetic resonance imaging (MRI).Patients and Methods The medical charts of adult patients diagnosed with CM1 at two referral neurosurgical centers between 2010 and 2017 were reviewed. The patients were either managed conservatively or surgically. We evaluated the patients clinically with the Chicago Chiari Outcome Scale (CCOS). The radiologic diagnosis was based on both craniocervical and PC-MRI.Results Ninety adult CM1 patients were managed conservatively. Conservative treatment failed in 5 of these 90 patients. Seventy-two patients (including those 5 patients who did not benefit from conservative treatment) underwent posterior fossa decompression with duraplasty. Eighty-five patients (94.4%) from the conservative group and 61 patients (84.7%) from the surgical group were treated successfully. An aqueductal stroke volume (ASV) value of 12 µL was found as the cutoff value for surgical candidates. A strong positive correlation between the increase in ASV values and clinical improvement was observed.Conclusions PC-MRI can help in the management and follow-up of adult CM1 patients. Conservative management is possible in selected symptomatic CM1 patients with a high ASV (ASV > 15 µL). Surgery should be considered in patients with an ASV ≤ 12 µL. CM1 patients with ASV ≤12 to >15 μL require close follow-up. Long-standing symptoms, severe sleep apnea, symptoms influencing functionality, and syrinx are factors that affected outcomes negatively.
Keywords: chiari malformation type I; conservative therapy; posterior fossa decompression with duraplasty; CSF flow MRI; phase-contrast MRI